Pengaruh Penambahan Puree Daun Kelor ( Moringa oleifera ) Terhadap Karakteristik Siomay Ayam - Yumiko Murdiasa, Putu; Suparthana, I Putu; Timur Ina, Putu (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 10 No 2 (2021): Jurnal ITEPA, 2021)
Dumpling is one type of dimsum, wich is a food that originates from China.The purpose of adding moringa leaf puree to chicken dumplings is to add antioxidant, vitamin C and crude fiber content to dumplings. The purpose of this research is to obtain the concentration of the addition of the appropriate Moringa leaf puree to produce chicken dumplings with the best characteristics. This research design used was a Completely Randomized Design with adding Moringa leaf puree wich consist by 5 levels: 0%, 10%, 20%, 30% and 40%. Each treatment was repaeat 3 times so that obtained 15 experimental units. The data obtained were analyzed by variance and if the treatment had significant effect followed by Duncan multiple range test. The results showed that the effect of adding moringa leaf puree had a significant effect (P<0,01) on moisture content, crude fiber, vitamin C, antioxidant activity, significant effect on ash content, color hedonic test, texture scoring test. The best treatment in this research was the addition of 40% moringa leaf puree with the following characteristics: 58.95% moisture content, 1.97% ash content, 2.18% crude fiber content, vitamin C 0.22 mg / g and antioxidant activity 38.30% with IC50 value 12342.28 ppm, the texture are very chewy and rather liked, the, the aroma, the taste and overall reception are  rather liked.